2021
DOI: 10.1021/acs.jproteome.0c00932
|View full text |Cite
|
Sign up to set email alerts
|

In Stallion Spermatozoa, Superoxide Dismutase (Cu–Zn) (SOD1) and the Aldo-Keto-Reductase Family 1 Member b (AKR1B1) Are the Proteins Most Significantly Reduced by Cryopreservation

Abstract: Although cryopreservation is widely used in animal breeding, the technique is still suboptimal. The population of spermatozoa surviving the procedure experiences changes attributed to alteration in their redox regulation. In order to expand our knowledge regarding this particular aspect, the proteome in fresh and frozen thawed aliquots of equine spermatozoa was studied to identify the proteins most severely affected by the procedure. If alteration of redox regulation is a major factor explaining cryodamage, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The presence or activity of AKR1B1 in ejaculated sperm has been demonstrated in equine (26), bovine (17,25) and porcine species (24). Similarly, the results of the peptide competition assay of the Western Blot showed a specific double-band pattern at 36 kDa and ~80 kDa in all ejaculated and epididymal sperm samples, thus suggesting that different forms of this protein could be physiologically present in pig sperm.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The presence or activity of AKR1B1 in ejaculated sperm has been demonstrated in equine (26), bovine (17,25) and porcine species (24). Similarly, the results of the peptide competition assay of the Western Blot showed a specific double-band pattern at 36 kDa and ~80 kDa in all ejaculated and epididymal sperm samples, thus suggesting that different forms of this protein could be physiologically present in pig sperm.…”
Section: Discussionmentioning
confidence: 67%
“…Although aldose reductases have been identified in bovine (17,25), equine (26) and porcine sperm (24), the origin of this protein in mature sperm cells is still unknown. In this regard, while translation during spermatogenesis could be a possibility, no previous study has confirmed if the relative content of AKR1B1 is higher in ejaculated than in epididymal sperm.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these proteins may be critical for gene expression regulation after embryo genome activation; the integrative analysis of the sperm, oocyte and blastocyst proteomes and transcriptomes revealed a set of embryo proteins with an exclusive paternal origin, some of which are crucial for correct embryogenesis and, possibly, for modulation of the offspring phenotype (Castillo et al 2018). In relation to this, cryopreservation is known to impact the sperm proteome (Bogle et al 2017; Martin-Cano et al 2020b; Gaitskell-Phillips et al 2021b; Gaitskell-Phillips et al 2021a). Taking all these findings in account, is likely that embryos produced with cryopreserved spermatozoa may experience alterations resulting of changes induced by cryopreservation in the proteome of the spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…This mitochondrial damage causes redox imbalance and accelerates different forms of sperm death, including necrotic, apoptotic (Aitken and Koppers 2011; Aitken and Baker 2013) and probably ferroptotic sperm mortality (Ortiz-Rodriguez et al 2020). In addition to protein degradation during cryopreservation, redox deregulation may induce oxidative damage to proteins causing notable modifications of the sperm proteome (Bogle et al 2017; Martin-Cano et al 2020a; Gaitskell-Phillips et al 2021b). All these modifications may affect proteins participating in the regulation and or survival of the early embryo (Castillo et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The same protocol as described in [3] , [4] , [5] , [6] , [7] , [8] , [9] was used. Stallion ejaculates were washed in PBS (600gx 10’), then the pellet formed by the spermatozoa was frozen immediately in liquid nitrogen and kept frozen at -80 °C.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%